Last Decade Insights in Exploiting Marine Microorganisms as Sources of New Bioactive Natural Products - Costanza Ragozzino; Vincenza Casella; Alessandro Coppola; Silvia Scarpato; Carmine Buonocore; Antonella Consiglio; Fortunato Palma Esposito; Christian Galasso; Pietro Tedesco; Gerardo Della Sala; Donatella de Pascale; Laura Vitale; et al. (Marine Drugs)
Marine microorganisms have emerged as prolific sources of bioactive natural products, offering a large chemical diversity and a broad spectrum of biological activities. Over the past decade, significant progress has been made in discovering and characterizing these compounds, pushed by technological innovations in genomics, metabolomics, and bioinformatics. Furthermore, innovative isolation and cultivation approaches have improved the isolation of rare and difficult-to-culture marine microbes, leading to the identification of novel secondary metabolites. Advances in synthetic biology and metabolic engineering have further optimized natural product yields and the generation of novel compounds with improved bioactive properties. This review highlights key developments in the exploitation of marine bacteria, fungi, and microalgae for the discovery of novel natural products with potential applications in diverse fields, underscoring the immense potential of marine microorganisms in the growing Blue Economy sector.